Learning from socially driven frugal innovation to design the future of healthcare: A case of mobile Primary Health Center - Md Haseen Akhtar; Janakarajan Ramkumar (Wiley, 2024)
Abstract Background and Aim Despite their flaws, the low‐cost but powerful economical solutions can ensure everyone has access to health. The main aim of this study is to extract characteristics of frugal innovation (FI) and social innovation (SI) for Primary Health Centers (PHCs) in low resource settings (LRS) for sustainable development. We will use the gained insights to design the mobile primary healthcare infrastructure using FI and SI strategies. There is a lack of methodology to design sustainable healthcare infrastructure for LRS. There is a gap in the literature about building sustainable infrastructure to provide basic healthcare facilities essential to the community. This article studies several factors necessary for designing sustainable infrastructure from the lens of FI, SI, and sustainability to develop a mobile healthcare infrastructure for last‐mile people. Methods Started with purposive sampled case studies to find out factors and criteria that most affect the success for an innovation to be frugal, social, and sustainable. The established criteria were used to design, develop, and deploy the mobile Primary Health Center (mPHC). Moving forward, we tested the system designed with stakeholders to gather insights. At this stage we found the feedback loop from the stakeholders and the role of interdisciplinary discussions between experts, medical officers, nurses, patient, and other staff of PHCs during the design, development, deployment, and test stage to be useful in taking design decisions efficiently. Results The designed healthcare infrastructure of mPHC through the aspects of FI and SI proves to be efficient in providing key healthcare services to LRS. Conclusion Focusing on essential capabilities and optimizing performance with technology, methodologies, and processes reduces costs in an innovation. Focus on socially inclusive and rebalancing power disparities, overcome societal challenges and improve human capabilities will create a sustainable and novel solution.